AI use in teaching module and assignment development: Reported practices from Indonesian EFL pre-service teachers - Fika Megawati; Sheila Agustina; Muhlasin Amrullah; Saltanat Meiramova; Fitria Wulandari; Tia Rahmahwati (Universitas Islam Malang, 2026)
The rapid development of artificial intelligence (AI) in education has not been matched by sufficient research on how pre-service English as a foreign language (EFL) teachers perceive the use of AI for developing instructional modules. This study explores these perceptions among pre-service EFL teachers from three universities in Indonesia who already have experience using AI. Most participants were female, in the final stage of their studies, and enrolled in a micro-teaching course. A survey was administered using an online questionnaire to investigate the practices and experiences of AI among pre-service teachers and analyzed using descriptive quantitative methods. The findings show that the pre-service teachers were enthusiastic yet cautious in using AI. Many used AI regularly, while others used it occasionally. They perceived clear benefits of AI, particularly in generating ideas, improving efficiency, and enhancing the quality of learning materials. AI was most commonly used to design lesson topics, develop content, and create test items. However, several challenges were identified, including plagiarism risks, inconsistent AI-generated outputs, and concerns about overreliance on AI. ChatGPT was the most frequently used tool, and participants expressed interest in more adaptive features that tailor content to students’ needs. The study recommends that AI use in teacher education be guided by instructors, with limited use in student assignments to maintain ethical standards and critical thinking skills. These findings provide valuable insights into AI literacy and pedagogical AI applications, contributing to the development of AI-adaptive teacher education curricula.